Winter Activity of Ants in an Urban Area of Western Japan - Hosoishi, Shingo; Rahman, Mamunur; Murakami, Takahiro; Park, Sang-Hyun; Kuboki, Yuzuru; Ogata, Kazuo (Sociobiology, 2019)
During winter, foraging activity of ants is considered low in temperate regions. Winter activity of ground-dwelling ants was investigated using bait traps and quadrat sampling in an urban area of Fukuoka City, western Japan. Six study sites were grouped into two categories: 4 open land types and 2 forest types. A total of 18 ant species were recorded between the end of January and beginning of March. The foraging activity of ants was generally low, except during relatively warm periods when the surface ground temperature was above 6℃–7℃ or soil temperature was above 4℃–5℃. Tetramorium tsushimae, Messor aciculatus, and Pheidole noda were the most abundant in the open land type, whereas Nylanderia flavipes, P. noda, and Crematogaster osakensis were the most abundant in the forest type. Bait preference varied among the different species, e.g., P. noda preferred tuna over honey, whereas N. flavipes similarly responded to tuna and honey. This is the first detailed study on the relationship between temperature and ant activity in Japanese mainland fauna.